The impact of phosphodiesterase-5 inhibitor (sildenafil citrate) on some hippocampal neurotransmitters, oxidative stress status, minerals, and anxiety-like behavior in rats (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The purpose of this work was to investigate the effect of phosphodiesterase type 5 (PDE-5) inhibitor sildenafil citrate (SC) on the level of brain hippocampal neurophysiological parameters (inhibitory and excitatory neurotransmitters), oxidant/antioxidant status, minerals, and anxiety-like behavior using albino male rats.Materials and methods: A total of 24 albino male rats were allocated to three separate groups (each one had eight rats): control and SC 5 and 10 mg/kg treatments via i.p. infusion every 3 days for 12 injections. For the behavior of anxiety evaluation, the elevated plus maze test was conducted 1 day after the last treatment, and then all the rats were killed. For serum separation, the blood samples were taken, and hippocampus was dissected from the brain and stored frozen until analysis.Results: Both doses of sildenafil significantly improved brain hippocampal neurotransmitter [norepinephrine, serotonin (5-hydroxytryptamine), and gamma-aminobutyric acid] values accompanied by a decreased dopamine level. Interestingly, the SC higher given dose (10 mg/kg) increased the malondialdehyde level with the reduction of the antioxidant parameters [reduced glutathione (GSH) level, catalase (CAT), and superoxide dismutase (SOD) activities] although the lower dose of SC did not cause oxidative stress. Serum and brain hippocampal K, Cu, and Se concentrations were also increased with SC treatments. Moreover, the test of elevated plus maze revealed an anxiolytic impact of sildenafil.Conclusion: It was concluded that SC improved the parameters of some hippocampal neurotransmitters and minerals accompanied by anxiolytic impact with the test of elevated plus maze, with a state of oxidative stress revealed with the higher dose of SC which was not recorded with the lower dose.Adv. Vet. Anim. Res., 7(2): 281-289, June 2020